2020
DOI: 10.1111/bjh.17004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of impaired dabigatran absorption following laparoscopic Roux‐en‐Y gastric bypass surgery: the Auckland regional experience (2011–2018)

Abstract: Additional supporting information may be found online in the Supporting Information section at the end of the article. Fig S1. (A) Unstimulated IFN-c levels (i.e. those measured in NIL Tube) of the 141 paediatric patients (age 0-18 years) tested with QFT-G in 2019 at Bambino Ges u Children's Hospital (red box indicates outliers). (B) Unstimulated IFNc levels of the 141 paediatric cases by age group (Brown-Forsythe ANOVA test).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The authors did not measure dabigatran plasma concentrations, but inferred from a normal APTT that the absorption of dabigatran might have been insufficient. In a retrospective case series of nine patients who underwent gastric bypass surgery, dabigatran peak concentrations were consistently lower than those reported in clinical trials [ 28 ]. Five of these nine patients were switched to rivaroxaban, and peak serum concentrations were comparable to the range reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The authors did not measure dabigatran plasma concentrations, but inferred from a normal APTT that the absorption of dabigatran might have been insufficient. In a retrospective case series of nine patients who underwent gastric bypass surgery, dabigatran peak concentrations were consistently lower than those reported in clinical trials [ 28 ]. Five of these nine patients were switched to rivaroxaban, and peak serum concentrations were comparable to the range reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies reported clinical outcomes only (n = 3145 patients), [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] three reported pharmacokinetic outcomes only (n = 3 patients), [32][33][34] and nine reported both clinical and pharmacokinetic outcomes (n = 81 patients). 15,[35][36][37][38][39][40][41][42] Only one study 17 compared DOACs with warfarin in patients with non-valvular atrial fibrillation after bariatric surgery and did not show a statistically significant difference in the rate of stroke or systemic embolism, or major bleeding between the two interventions (Table S2).…”
Section: Ta B L Ementioning
confidence: 99%
“…We identified 2519 records through database searches, http://clinicaltrials.gov, and reference lists (Figure 1). Twenty‐eight studies were included: 7 cohort studies, 6 case series, and 15 case reports 15–42 . Study characteristics can be found in Table 2.…”
Section: What Is the Efficacy And Safety Of Doacs After Bariatric Sur...mentioning
confidence: 99%
“…The drug concentration decreased significantly. According to the researchers, this may indicate impaired or delayed absorption [52]. Rottenstreich et al, observed that the C max of dabigatran in BS patients regularly using this drug was within the expected range [53].…”
Section: Anticoagulant Drugsmentioning
confidence: 99%